Analisis Akuisisi Kemampuan Kognitif dan Psikomotorik Peserta Didik Kelas III SD Nurul Sakinah Azzahra dalam Pembelajaran IPA pada Materi Ekosistem dan Rantai Makanan - rahmi zahirah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
Science education at the elementary level plays a crucial role in fostering students’ scientific thinking skills and practical abilities. This study aims to explore and describe the development of cognitive and psychomotor competencies in science learning among third-grade students at SD Nurul Sakinah Azzahra, with a specific focus on the topic of ecosystems and food chains. A qualitative descriptive–exploratory design was employed to capture the learning experiences of 21 purposively selected participants. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that contextual and experiential learning approaches significantly enhanced students’ understanding of ecological relationships and their ability to represent food chain concepts accurately. Students actively engaged in observing plants and animals within their school environment, classifying organisms into producers, consumers, and decomposers, and creating simple visual models of energy transfer. Cognitive growth was evident in students’ improved ability to explain interdependence among living organisms using logical reasoning, while psychomotor development was reflected through improved observation, recording, and drawing skills. The teacher’s role as a facilitator was central to encouraging exploration, collaboration, and inquiry-based learning. Although challenges such as limited time, instructional resources, and diverse student abilities were encountered, these were effectively managed through adaptive teaching strategies and contextualized learning activities. In conclusion, the study demonstrates that contextual and exploratory science instruction fosters not only conceptual understanding but also curiosity, creativity, and environmental awareness among young learners. These findings emphasize the importance of implementing active, student-centered learning approaches in elementary science education to promote holistic cognitive, psychomotor, and affective development.